Investigation of PC cluster productivity in quantum mechanical molecular computations - Pankevičius, Egidijus; Rakauskas, Rimantas-Jonas; Šulskus, Juozas; Vošterienė, Svajonė (Lietuvos matematikos rinkinys, 2003)
There is not abstract.